Riasan Wajah Sebagai Bagian Gambar Diri: Bukan Sekadar Kewajiban atau Hasrat - Irene Chrysantheme Roan Pea (Indonesian Journal of Theology, 2020)
This paper discusses the image of the human body as an important existential component amid the totality of existence in its socio-communal construction. Body image is itself constructed upon one’s impressions, thoughts, feelings, and opinions about one’s own body. In light of the proliferation of beauty vlogger accounts on various social media platforms (YouTube and Instagram) demonstrating various makeup techniques for women, the author sets forth a reconstructive critique [kritik rekonstruksi] against the hustle-and-bustle of modernism that traps humanity within the assemblage of an industrialist-colonialist gaze that proclaimes makeup (facial cosmetics) to be constitutive for humanity’s self-image, particularly impacting women. The author argues that human persons are, in truth, creatures of beauty and worth in the authenticity of their self-image even without the aide of makeup, by considering the concept of ‘body image’ within the realm of psychology in addition to the theological aesthetic perspective of Hans Urs von Balthasar.